Emotional hedging : a football fan's perspective. - Chua, Glen Yongcheng. (2009)
The concept of "emotional hedging" advocates insuring against an undesired outcome so that the payout can be used to offset the negative feelings generated by this outcome. Many studies have established that risk-averse individuals are more likely to engage in hedging behaviour in the financial context. The aim of this graduation project is to study whether this result applies for "emotional hedging", particularly from the perspective of a football team supporter. The primary data for this research was collected by the means of a survey which was conducted on 250 local football fans. Our findings showed that risk aversion is positively related to a football fan’s willingness to take up a hypothetical insurance plan that gives a payout each time his supported team loses. However, there was no evidence that risk-averse fans are more willing to bet against their team as compared to risk-loving fans.